An improved criterion for evaluating the efficiency of two-electron integral algorithms - Frisch, Michael J.; Johnson, Benny G.; Gill, Peter M.W.; Fox, Douglas J.; Nobes, Ross H. (Chemical physics letters, 1993)
We present a general criterion for theoretical performance assessment of algorithms for two-electron integral computation which is appropriate for most modern computers. The new prescription is to minimize the total number of memory references in the algorithm, as opposed to the traditional approach of minimizing the total number of floating-point operations. CPU timings on a range of machines demonstrate that memory operations are better correlated to machine cycles than are floating-point operations.